A Cross-Sectional Review of Energy Transition, Security and Climate Change Policies - Georgescu, Cătălina Maria; Olimid, Anca Parmena; Olimid, Daniel Alin; Gherghe, Cosmin Lucian (Dr. Viktor Koval, 2025)
Introduction. Energy, security, and climate change are essential concerns for policymakers and economic agendas, prioritising data monitoring, national resources, resilience, and informed planning. The analysis of these topics is relevant for achieving sustainability objectives and targets, especially for understanding and analysing societal, technological, environmental, and economic developments, aiming to guarantee a fair and inclusive transition. Aim and tasks. This study presents a legal and policy nexus linking energy transition, security, and climate change by completing a complex analytical and conceptual analysis of key terms and policies developed from 1985 to 2022. Furthermore, it reviews the evolution of climate change, security, and energy transition concepts and analyses European and international policy and judicial options to reach a consensus on addressing climate change. Results. The findings are intended to provide insights into the nexus of energy-security-climate change by reflecting the terminology and associated concepts in digitalised academic literature from 1985 to 2022 using the Google Ngram Viewer platform. The modelling analysis displayed various interrelated graphical representations that support future green energy and climate change policy settings, linking Ngram monitoring, result analysis, and data interpretation. The cross-sectional analysis examines the dynamic conceptual processes of specific terms and emerging research streams on security and climate change over four decades. The findings show linkages between climate change, sustainability, renewable energy, energy security and new conceptual associations that influence diverse academic research. Pearson correlation for statistical analysis results showed strong dependencies between variables, consistent with the values represented using the Google Ngram Viewer platform. Conclusions. This study provides an overview of the circulation of concepts in the energy and climate change sectors within digitalised academic literature, mapping emergent conceptual trends over the selected period. The visualisation of the modelling analysis correlates with the temporal frequencies, as classified by the research sections. It organises data using graphical representations of energy resources and climate change concerning sustainable development and security.